c. \( 3 \times 2-3 \times 1=(3 \times 2)-(3 \times 1)=(33(2-1) \) If \( a=3, b=2 \) and \( c=4 \), calculate the following: Example: \( \quad a(b+c)=a \times b+a \times c \) \( 3(2+4)=3 \times 2+3 \times 4 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
Let's break this down using the values you provided! First, we have: \( a(b+c) = a \times b + a \times c \) Substituting \( a = 3 \), \( b = 2 \), and \( c = 4 \): \( 3(2+4) = 3 \times 2 + 3 \times 4 \) Calculating this step-by-step: Left side: \( 3(6) = 18 \) Right side: \( 3 \times 2 = 6 \text{ and } 3 \times 4 = 12 \) So, \( 6 + 12 = 18 \) Thus, \( 3(2+4) = 3 \times 2 + 3 \times 4 \) holds true! Now for your equation: \( 3 \times 2 - 3 \times 1 = (3 \times 2) - (3 \times 1) = 3(2 - 1) \) Let’s compute this: Left side: \( 3 \times 2 = 6 \text{ and } 3 \times 1 = 3 \) So, \( 6 - 3 = 3 \) Right side: \( 3(2 - 1) = 3(1) = 3 \) Both sides match, confirming that \( 3 \times 2 - 3 \times 1 = 3(2 - 1) \) is also correct!